O potrzebie monograficznych opracowań przedsiębiorstw - Wesołowski, Aleksander (Wydział Prawa i Administracji UAM, 1987)
The monographical method and the monographs on different social groups may be, contrary to some opinions, very useful for collecting factographical materials and their subsequent analysis. The author advocates preparing possibly complex monographs on industrial enterprises since such monographs are indispensable to formulate the theory of an industrial enterprise. He points at the existing approach to the sociological monographs on the factory crew and he suggests a scheme of issues useful for the research on the social function of an industrial enterprise.
On the Need for Monographical Studies of Enterprises